Memoirs as a source on the history of first teachers’ everyday life - Nadezhda Ochur, Vera Damdynchap, (Opción, 2019)
The article discusses the daily routine of the first Russian teachers in Tuva on the basis of their memories. Based on the methodology of oral history, the authors reveal the daily life of the first Russian teachers in Tuva. As a result, a rather large material of oral historical sources was collected that revealed the peculiarities of the teachers’ everyday life, their experiences and feelings during the period of social changes. As a conclusion, the teachers’ memories fill the history of Tuva with the human dimension, making its understanding closer to the younger generation